Safety and Efficacy of Tocilizumab for the Treatment of Rheumatoid Arthritis - Atsushi Ogata; Tôru Hirano; Yoshihiro Hishitani; Toshio Tanaka (2012)
Because of the pathological role of IL-6 in rheumatoid arthritis (RA), tocilizumab (TCZ), a humanized anti-IL-6 receptor monoclonal antibody, was expected to improve inflammation and joint destruction of RA. Indeed, randomized clinical trials demonstrated the clinical efficacy of TCZ as monotherapy or combined with methotrexate (MTX) for RA patients with inadequate responses to disease-modifying antirheumatic drugs, MTX or tumor necrosis factor (TNF) inhibitors. Although long-term tolerability for TCZ is superior to that for TNF inhibitors, information regarding the potency of drug free remission of TCZ is limited at present. In terms of its safety profile, the general risk of infection when using TCZ is comparable to that of TNF inhibitors. TCZ has some advantage in RA patients who can not use MTX and are non-responders to TNF inhibitors. In conclusion, TCZ is one of the most prospective next generation biologics for the treatment of RA.